South African General Equity Unit Trust Funds:Fund Performance and Characteristics - Pardoe, Liam (Department of Finance and Tax, 2019)
We evaluate performance of general equity unit trust funds in South Africa during the period 2010 to 2017 and identify, if any, characteristics of these unit trust funds that are drivers of this performance. Performance is measured using Jensen’s Alpha with a sample that has not suffered from the full effects of survivorship bias as many other South African research studies have in past years. We used a Weighted Least Squares regression model, after weighting each funds Jensen’s alpha, to determine what characteristics impact the performance of unit trust funds. Our results showed that Beta, Fund Age, Percentage of Top 10 Holdings and Management Fees were all significant in explaining unit trust performance. We found that in the South African general equity unit trust space, funds which take higher risk relative to the market will experience higher levels of performance, younger funds tended to outperform their older counterparts and funds that charge lower management fees will outperform those with higher fees. Funds that on average throughout the period held less Top 10 JSE listed equity stocks tended to outperform those having a larger Top 10 holding exposure. We have thus been able to uncover material performance characteristics that differentiate South African unit trust performance. We have also provided meaningful parameters for investors and investment managers when structuring diversified portfolios, allowing them to improve their ability to provide outperformance consistently over time.